(untitled) (Third Sector Social Economic Review, 2017)
The concept of sustainable development was presented first in World Commission on Environment and Development (Brundtland Commission) report in 1987 and defined as ""development which meets the needs of current generations without compromising the ability of future generations to meet their own needs"". In this context, adopting economic participation and democratic control as principle, cooperatives have a most important role in sustainable development. To perform this role cooperatives should sustain their entity. In this study we examined the financial incentive mechanisms in renewable energy cooperatives in Turkey and developed countries. Finally, suggestions and criticism about the subject were stated.